2014
DOI: 10.1037/cns0000022
|View full text |Cite
|
Sign up to set email alerts
|

A brief mindfulness and yoga intervention with an entire NCAA Division I athletic team: An initial investigation.

Abstract: Whereas traditional sports psychology interventions emphasize controlling or reducing distress, mindfulness-based interventions teach tolerance and acceptance of negative thoughts, feelings, and emotions. In the present pilot study, an entire men's Division I athletic team (n ϭ 13) provided voluntary consent and participated in a brief mindfulness-based intervention. Over 5 weeks, the team attended eight 90-min group intervention sessions immediately followed by 1-hr Hatha yoga sessions. Completer analyses sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(95 citation statements)
references
References 81 publications
3
76
0
16
Order By: Relevance
“…Benefits of increasing mindfulness and positive thinking promotes mental flexibility by accepting observations and acting within personal values. 6 Student-athletes who participated in a mindfulness-based intervention demonstrated higher goal directed energy, as well as increased awareness and attention. These traits can be transferrable to improved sport participation such as increased awareness and internal focus on specific tasks, and enhanced decisionmaking skills during different situations.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…Benefits of increasing mindfulness and positive thinking promotes mental flexibility by accepting observations and acting within personal values. 6 Student-athletes who participated in a mindfulness-based intervention demonstrated higher goal directed energy, as well as increased awareness and attention. These traits can be transferrable to improved sport participation such as increased awareness and internal focus on specific tasks, and enhanced decisionmaking skills during different situations.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
“…5 Regardless of the method of mindfulness used, all 3 studies supported the utility of this strategy as a way to potentially mitigate emotional stress and/or physical injury. Two studies 5,6 found the use of mindfulness-based interventions to be effective for increasing mindfulness and positive thinking in student-athletes. Benefits of increasing mindfulness and positive thinking promotes mental flexibility by accepting observations and acting within personal values.…”
Section: Implications For Practice Education and Future Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Esto se sostiene dados los resultados de investigaciones antecedentes, en donde se ha observado una relación inversa entre la conciencia plena y rumiación (Raes y Williams, 2010;Sauer y Baer, 2012); así como una relación directa entre la práctica del yoga y la conciencia plena (Shelov y Suchday, 2009;Wolever et al, 2012;Goodman et al, 2014).…”
unclassified